The Thromboplastinogen activity time (TAT) Test - Quick, Armand J. (Thrombosis and Haemostasis, 1957)
The thromboplastinogen activity time (TAT) test is described. The method is based on the finding that rabbit brain extract heated to 60° C loses its holo-thromboplastin activity but retains the properties of platelet extract and can, therefore, be used as a substitute for platelet extract in the prothrombin consumption test. The application of the test to differentiate hemophilia from thrombocytopenia and thrombasthenia is illustrated by case reports. The use of the test for the differential diagnosis of hemophilia and PTC deficiency is outlined and examples of its application given.